Ab initio atomic thermodynamics investigation on oxygen defects in the anatase TiO2 - Cheng, Zhijun; Liu, Tingyu; Yang, Chenxing; Gan, Haixiu; Chen, Jianyu; Zhang, Feiwu (Journal of alloys and compounds, 2013)
► Three typical oxygen defects under the different annealing conditions have been studied. ► The oxygen vacancy is easier to form at the surface than in the bulk. ► The adsorption of O2 whose orientation is parallel to the surface should be more favorable. ► The reduction reaction may firstly undertake at the surface during the annealing treatment. ► The interstitial oxygen has important contribution to lead to the reduction of the band gap. In the framework of the ab initio atomic thermodynamics, the preliminary analysis of the oxygen defects in anatase TiO2 has been done by investigating the influence of the annealing treatment under representative conditions on three typical oxygen defects, that is, oxygen vacancy, oxygen adsorption and oxygen interstitial. Our results in this study agree well with the related experimental results. The molecular species of the adsorbed O2 is subject to the ratio of the number of the O2 to that of the vacancy, as well as to the initial orientation of O2 relative to the surface (101). Whatever the annealing condition is, the oxygen vacancy is easier to form at the surface than in the bulk indicating that the reduction reaction may firstly undertake at the surface during the annealing treatment, which is consistent with the phase transformation experiments. The molecular ion, peroxide species, caused by the interstitial oxygen has important contribution to the top of the valence band and lead to the reduction of the band gap.